2020
DOI: 10.1093/toxres/tfaa012
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neoplastic and immunomodulatory potency of co-treatment based on bovine lactoferrin and/or muramyl dipeptide in tumor-bearing mice

Abstract: The current study investigates anti-neoplastic and immunomodulatory activities of co-treatment based on bovine lactoferrin (bLF) and/or muramyl dipeptide (MDP) with or without cisplatin (Cis) in tumor-bearing mice. In the present study, bLF (100 mg/kg; orally) and MDP (0.5 mg/kg; subcutaneously) was administered alone or together. MDP or bLF was co-treated with Cis (1 mg/kg; intraperitoneally) in mice-bearing Ehrlich solid carcinoma. Tumor size, tumor mass proliferation, apoptosis using immunohistochemistry, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Similar to earlier findings, an escape strategy of the tumour cells, the tumour microenvironment was characterised by the proliferation of particular cell types such as regulatory T cells (CD4 + CD25 + ) in order to suppress the protective antitumor immunity 47 53 . In accordance , Ibrahim et al 54 clarified that tumor development was linked to a decrease in the percentage of splenic CD3 + CD8 + cell population in Ehrlich solid tumor bearing mice. Furthermore, cinnamon effectively restored the balance of T-cell subsets by promoting the proliferation of T helper-1 and T cytotoxic 1 while reducing the proliferation of regulatory T cells in SLTBI mice and augmenting the IFN-γ production and strengthening the antitumor effect against lung metastasis of melanoma in SLTBI mice 55 .…”
Section: Discussionmentioning
confidence: 61%
“…Similar to earlier findings, an escape strategy of the tumour cells, the tumour microenvironment was characterised by the proliferation of particular cell types such as regulatory T cells (CD4 + CD25 + ) in order to suppress the protective antitumor immunity 47 53 . In accordance , Ibrahim et al 54 clarified that tumor development was linked to a decrease in the percentage of splenic CD3 + CD8 + cell population in Ehrlich solid tumor bearing mice. Furthermore, cinnamon effectively restored the balance of T-cell subsets by promoting the proliferation of T helper-1 and T cytotoxic 1 while reducing the proliferation of regulatory T cells in SLTBI mice and augmenting the IFN-γ production and strengthening the antitumor effect against lung metastasis of melanoma in SLTBI mice 55 .…”
Section: Discussionmentioning
confidence: 61%
“…Ibrahim et al. ( 46 ) investigated the antitumor and immunomodulatory effects of co-treatment based on MDP with or without Cis and bovine lactoferrin (bLF) in mice with Ehrlich solid tumor (ESTs). It was concluded that the combination of MDP and bLF could stimulate an innate but also an adaptive immune response, and this could lead to an optimal therapeutic immune response in an Ehrlich carcinoma murine model.…”
Section: Potential Anticancer Activity Of Mdp Analogs: Cellular and A...mentioning
confidence: 99%
“…Lf has been confirmed to enhance the adaptive immune response and is an effective anti-inflammatory drug (63). Although its molecular mechanism still needs to be revealed, researchers have found that both hLf and bLf can enter the host cell nucleus and bind to DNA to regulate gene expression, thereby exerting their anti-inflammatory activity (64).…”
Section: Lf Is a Natural Immune Modulator Involved In The Antitumor R...mentioning
confidence: 99%